Evaluating micromobility adoption, perception, and implementation - Pourfalatoun, Shiva, author; Gallegos, Erika, advisor; Daily, Jeremy, committee member; Simske, Steve, committee member; Bradley, Thomas, committee member; Jin, Ziyu, committee member (Colorado State University. Libraries, 2024)
Micromobility, a term that encompasses compact and efficient transportation modes such as bicycles and scooters, has rapidly emerged as an important element of urban mobility. These small, often electrically-powered vehicles offer a versatile solution to urban congestion and provide an eco-friendly alternative to traditional transportation modes. Particularly, shared bicycles and e-scooters have become popular due to their convenience and accessibility, offering significant benefits but also presenting new challenges in urban planning and traffic management. This transition in urban transport paradigms raises several pertinent questions about user behaviors, preferences, and the interplay of various socio-psychological factors. This dissertation aims to explore three key aspects of micromobility. The first research question investigates the differences between shared e-scooter users and non-users, along with the factors influencing their decisions regarding e-scooter usage. The second question examines the shift in micromobility preferences and perceptions before, during, and after the COVID-19 pandemic, focusing on how these changes correlate with different quarantine behaviors. The third and final question delves into the interactions between drivers, bicyclists, and pedestrians, analyzing how drivers' risk-taking propensity and emotional intelligence influence these interactions. Each of these questions is approached through specific methodological frameworks, employing a mix of statistical analyses and behavioral observations to provide insights into the evolving dynamics of urban mobility. The findings from this research provide a systematic approach to integrating micromobility, by understanding at the individual level the factors that effect decision-making on usage, as well as interaction effects with other road users that impact safety.